Biological Therapy Methods in Modern Psychiatry: Antidepressants, Neuroleptics and their Effectiveness - Uzokboyevich, Turgunboyev Anvar (American Journal of Bioscience and Clinical Integrity, 2025)
All aspects of the organization of psychiatric care are concentrated in the treatment of mentally ill people: the provision of medical institutions with medicines and materials, the qualification and training of doctors and medical workers. Modern differential diagnostic, clinical and organizational, therapeutic and rehabilitation methods of providing care to patients not only complement each other, but also allow the "realization" of each of these relatively independent areas of medical care. The absence of one or another connection or its "blocking" affects the entire system of providing care to mentally ill people and in some cases can lead to its complete ineffectiveness. Treatment of any mentally ill person includes a number of medical (examination and diagnostics, emergency medical care, course therapy using various medications, psychotherapy, physiotherapy) and socio-therapeutic measures aimed at his socio-psychological correction and rehabilitation.